A construção gramatical de hiperbolização: um caso de coerência metafórica da gramática - Bronzato, Lucilene Hotz (2010)
The present study aims at investigating the founding role that metaphor plays in the production and interpretation of what is referred to in this thesis as the Grammatical Construction of Hyperbolization (GCH). This construction is characterized, in the axis of form, by its being structured, in Portuguese, by a causative verb of destruction, such as arrasar (to wipe out) detonar (to detonate), destruir (to destruct) and arrebentar (to burst), among others, without its complement. In the axis of meaning, on the other hand, the pragmatic-semantic inference, together with the grammatical construction under study, is the hyperbolization and the hypervalorization of the force of action of the subject-entity, which places it at the top of an evaluative scale. Instantiated in utterances such as A nova musa do carnaval arrasou na avenida , the Construction of Hyperbolization reflects the metaphorical mapping of the source domain of WAR onto the target domain of SUCCESS, pervasive in our culture and in our everyday language, as our corpus analysis has evidenced. The semantic-pragmatic function of the construction is, therefore, to reframe the domain of destruction, evoked by the verb, into the domain of success, evoked by the GCH through a highly coherent system of metaphoric and metonymic implications.